Trips and trade - Volker Nitsch (Technische Universität Darmstadt, Department of Law and Economics, 2018)
Politicians travel a lot, for various reasons. The types of trips to foreign countries range, for instance, from a formal, highly-orchestrated, multi-day visit to brief logistical stop-overs, from the regular exchange of information during official talks in a working environment to ceremonial visits. This chapter reviews selected issues in the analysis of the economic effects of foreign travels by politicians. It starts by highlighting possible differences in the effects dependent on the visitor's official position. Next, it is emphasized that only few travels, dependent on their purpose, may be economically relevant. Finally, issues related to the choice of the travel destination are discussed.
urn:nbn:de:tuda-tuprints-72859
Keywords: 330; diplomacy; visit; travel; official; host